2022
DOI: 10.3390/s22103682
|View full text |Cite
|
Sign up to set email alerts
|

Evolution Characteristics of Seismic Detection Probability in Underground Mines and Its Application for Assessing Seismic Risks—A Case Study

Abstract: Seismic hazards are typical mining hazards causing dynamic failure of coal and rock mass, which greatly threatens the safety of personnel and equipment. At present, various seismic analysis methods are used to assess seismic risks but their accuracy is significantly limited by the incompleteness of seismic data. The probability of detecting earthquakes (PDE) method has been proven as a powerful means for retrieving missed seismic events and enhancing the seismic data integrity in mines. However, to date, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Wang and colleagues proposed a workflow for reprocessing seismic data aimed at improving the quality of seismic data to better analyze changes in seismic activity [29,30]. Li and others investigated the evolution characteristics of the detection probability of seismic monitoring systems during the retreat mining period of coal mining faces and further correlated highly integrated seismic data with seismic risk [31].…”
Section: Introductionmentioning
confidence: 99%
“…Wang and colleagues proposed a workflow for reprocessing seismic data aimed at improving the quality of seismic data to better analyze changes in seismic activity [29,30]. Li and others investigated the evolution characteristics of the detection probability of seismic monitoring systems during the retreat mining period of coal mining faces and further correlated highly integrated seismic data with seismic risk [31].…”
Section: Introductionmentioning
confidence: 99%
“…These are very real issues that mining companies have to consider when it comes to providing safe working conditions for their employees. One of these is a seismic hazard that occurs in underground mines [3]. This type of natural hazard is incredibly difficult to detect and predictable, making it one of the most common threats in the mining industry.…”
Section: Introductionmentioning
confidence: 99%
“…Based on dynamic static energy principles, He et al [28] studied the precursory rules of coal bumps combined with electromagnetic emission and microseismic monitoring, and established a coupling evaluation system according to the monitoring results of a coal mine. Li et al [29] investigated the effect of the number of seismic data used for calculations and modifications to the arrangement of seismic monitoring transducers on the method of detecting earthquake probability. It can be concluded that these research results are mainly about risk assessment considering different geological factors.…”
Section: Introductionmentioning
confidence: 99%